To determine if the values \( x = -34, -12, \) and \( 12 \) are solutions to the quadratic equation \(-2x^2 - 3x + 2 = 0\), we will substitute each value into the equation and evaluate.
Here’s how to do it step by step for each value:
-
For \( x = -34 \):
\[
-2(-34)^2 - 3(-34) + 2
= -2(1156) + 102 + 2
= -2312 + 102 + 2
= -2312 + 104
= -2208 \quad (\text{Not } 0)
\]
-
For \( x = -12 \):
\[
-2(-12)^2 - 3(-12) + 2
= -2(144) + 36 + 2
= -288 + 36 + 2
= -288 + 38
= -250 \quad (\text{Not } 0)
\]
-
For \( x = 12 \):
\[
-2(12)^2 - 3(12) + 2
= -2(144) - 36 + 2
= -288 - 36 + 2
= -288 - 34
= -322 \quad (\text{Not } 0)
\]
Summary of Evaluations:
- For \( x = -34 \): evaluation resulted in \(-2208\)
- For \( x = -12 \): evaluation resulted in \(-250\)
- For \( x = 12 \): evaluation resulted in \(-322\)
Conclusion:
None of the values provided (−34, −12, or 12) satisfy the equation \(-2x^2 - 3x + 2 = 0\) since they do not produce a result of 0.
Therefore, the statement should be:
Only \( x = \) (none of the options provided) is in the solution set. In other words, none of the given values are in the solution set of the equation.